Managing Rare Disease for Practicing Primary Care Physicians - Cipta Mahendra (Faculty of Medicine, Public Health, and Nursing, 2021)
Primary care physicians (PCPs) are trained to provide care for a wide scope of medical conditions within their patient population. They are supposed to be the very first healthcare provider the patient should visit when having an illness. Accordingly, it is customary for PCPs to encounter many types of patient cases in their practice. In addition to common diseases, some patients may present with symptoms of a rare disease (RD).Unfortunately, PCPs often lack knowledge to promptly detect and manage the patients with such disease. A research from Ireland reveals that only a third of PCPs were able to establish a diagnosis for RD and refer the patient to the appropriate specialist1. In Spain, more than half the PCPs were deemed fair or poor in knowledge of RD2. Similar result was also obtained from an expert survey in Belgium, stating that the basic RD knowledge of most PCPs in the country is low3. It is therefore justifiable for Evans to say that many patients with RD are un- or misdiagnosed4 and thus, it may take years to finally get a correct diagnosis3. In Indonesia, there has been no published local- or nationwide research surveying the PCP’s knowledge concerning presentations of RD.